Jets of three-phase power-law fluids and foam jet mixing in gypsum slurry. (30th March 2018) - Dannessa, D.; Sinha-Ray, S.; Jun, S.; Yarin, A.L.
Highlights: Mixing of foam with gypsum slurry can be described in the framework of the boundary layer theory. The smaller the diffusion coefficient, the weaker the foam mixing. The higher the water-stucco ratio, the better the foam mixing. The higher crossflow velocities and the lower obliquity angles cause poorer mixing. Abstract: Gypsum wallboard is one of the major components of lightweight construction throughout the world. There have been significant efforts in manufacturing lightweight wallboard. One of the key elements of the manufacturing process is mixing foam in gypsum slurry. However, the dynamics of foam mixing in gypsum slurry is not fully explored and understood, which results in a trial-and-error based approach in the process optimization. In the present work, we study foam jet injection into gypsum slurry at rest and in cross-flow. The experimental part of the works reveals the foam/gypsum slurry rheological behavior. Namely, the foam-gypsum slurry mixtures are power-law fluids with the consistency and behavior indexes strongly depending on the local foam content. The submerged jet-like flows of foam/gypsum slurry mixtures belong to the class of the boundary layer problems of strongly non-linear power-law fluids of three-phase media (gypsum stucco, water and air), which is insufficiently studied in the framework of the non-Newtonian fluid mechanics. Moreover, jet propagation in cross-flow is studied here for the first time. Accordingly, a novel numerical approach to this class of problems is proposed and implemented in the theoretical part of the work, and the effect of several governing parameters [e.g., water-to-stucco ratio by mass (WSR), the Schmidt number, etc.] on the flow structure and the mixing rate is evaluated. The theoretical framework described here has a broader importance for multiple technologies related to material processing, and in particular, to formation of gypsum wallboard, since it allows one to predict the effective penetration depth of a jet, and thus, the foam/slurry mixing efficiency and the apparatus size.